2021
DOI: 10.1002/alz.12476
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alzheimer's disease and related dementias among veterans experiencing housing insecurity

Abstract: Introduction:Housing insecure veterans are aging, but the prevalence of Alzheimer's disease and related dementias (AD/ADRD) in the population is unknown. Methods:We calculated the prevalence of AD/ADRD diagnoses in 2018 among veterans that experienced homelessness, were at-risk for homelessness, or were stably housed. We determined acute care (emergency department, hospitalizations, psychiatric hospitalizations), and any long-term care (nursing home, and community-based) use by housing status among veterans wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
(72 reference statements)
0
23
0
Order By: Relevance
“…Keigher and colleagues (1992) also established that homeless patients were significantly more likely to be Black relative to the larger population. This finding was reiterated by Jutkowitz et al (2019, 2021a, 2021b) in homeless veteran populations. They also found that homeless veterans upon admission to a nursing home were younger (62.5 years vs. 75.3 years) and more likely to present with an alcohol abuse disorder (ARR = 2.18; 95% CI = 2.05–2.31) or drug use disorder (ARR = 3.03; 95% CI = 2.74–3.33), along with a non-specified mental health disorder diagnosis (ARR = 1.49; 95% CI = 1.45–1.54)…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Keigher and colleagues (1992) also established that homeless patients were significantly more likely to be Black relative to the larger population. This finding was reiterated by Jutkowitz et al (2019, 2021a, 2021b) in homeless veteran populations. They also found that homeless veterans upon admission to a nursing home were younger (62.5 years vs. 75.3 years) and more likely to present with an alcohol abuse disorder (ARR = 2.18; 95% CI = 2.05–2.31) or drug use disorder (ARR = 3.03; 95% CI = 2.74–3.33), along with a non-specified mental health disorder diagnosis (ARR = 1.49; 95% CI = 1.45–1.54)…”
Section: Resultsmentioning
confidence: 80%
“…Jutkowitz et al (2019) established that homeless veterans were younger upon admission to skilled nursing facilities and were more likely to have dementia than their stably housed counterparts (adjusted risk ratio (ARR) = 1.14, 95% CI = 1.04–1.25). In another study (Jutkowitz et al, 2021b), it was established that the risk for dementia in all homeless veterans treated at VA facilities was 1.58 (CI = 1.51–1.66), while the ARR in at-risk veterans was 2.98 (95% CI = 2.81–3.16), compared to stably housed counterparts. Bennett and colleagues (2009) did not use a VA database to establish dementia.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study of veterans revealed that the prevalence of Alzheimer disease and related dementias was higher among housing insecure veterans than those who were stably housed. 39 Epidemiologic studies have shown that those who are homeless experience higher rates of cardiovascular events, including stroke, compared with the general population. 40,41 Despite the plethora of research on the association between housing and health in general, more research is needed to explore the relationship between housing and neurologic conditions and whether interventions aimed at addressing housing affect neurologic health.…”
Section: Housingmentioning
confidence: 99%
“…21 ), including a recent publication in this journal 22. Our definition also overlaps substantially with the Chronic Conditions Data Warehouse definition of "Alzheimer's disease or related disorders or senile dementia" (https://www2.ccwdata.org/web/guest/conditioncategories-chronic), which is used for monitoring Centers for Medicare & Medicaid Services (CMS) data.…”
mentioning
confidence: 99%